A new approach to estimating AIDS incubation times: results in homosexual infected men. Issue 6 (December 1992) - Chevret, S; Costagliola, D; Lefrere, J J; Valleron, A J
Abstract : STUDY OBJECTIVE–The aim was to develop a new approach for estimating the incubation period of acquired immunodeficiency syndrome (AIDS), based on age distributions. DESIGN–Incubation period was expressed as the difference between age at time of diagnosis and age at time of contamination. Assuming independence between age at time of infection and incubation period, the age distribution of newly diagnosed AIDS cases is thus the convolution product between the distributions of the age of freshly infected patients and of the incubation times. AIDS incubation time can therefore be estimated from the age distribution of newly HIV infected subjects and newly diagnosed AIDS cases. SUBJECTS–Subjects were 2220 AIDS cases diagnosed until 1987, reported to the Ministry of Health, France, and 172 subjects discovered to be HIV-1 seropositive during a blood donation in Paris between August 1985 and July 1988. In both groups, the only known risk factor was homosexuality. MAIN RESULTS–The estimated median incubation time was 9.9 years (90% CI 9.0-10.9 years). Confidence intervals were narrow, even when taking into account the uncertainty in serodetection delay (90% CI 6.7-13.5 years). CONCLUSIONS–The incubation estimate is as accurate as previous estimates based on other models. This technique could therefore be applied to other risk groups.